Structural and Functional Brain Alterations in Populations with Familial Risk for Depression: A Narrative Review. Issue 6 (November 2022) - Burhanoglu, Birce Begum; Gonul, Ali Saffet
Abstract : Learning objectives: After completing this activity, practitioners will be better able to: Discuss the association between brain alterations and vulnerability or resilience to MDD in people with familial risk Define how structural and functional brain alterations associated with vulnerability or resilience could lead to a better understanding of the pathophysiology of MDD Aim: Familial history is associated with an increased risk for major depressive disorder (MDD). Despite the increased risk, some members of the familial high-risk population remain healthy, that is, resilient. Defining the structural and functional brain alterations associated with vulnerability or resilience could lead to a better understanding of the pathophysiology of MDD. This study aimed to review the current literature and discuss the association between brain alterations and vulnerability or resilience to MDD in people with familial risk. Methods: A literature search on MRI studies investigating structural and functional alterations in populations at familial risk for MDD was performed using the PubMed and SCOPUS databases. The search was conducted through June 13, 2022. Results: We reviewed and summarized the data of 72 articles (25 structural MRI, 35 functional MRI, 10 resting-state fMRI, one structural/functional MRI combined, and one structural/functional/resting-state fMRI combined). These findings suggested that resilience in high-risk individuals is related to the amygdala structure, frontal lobe activity, and functional connectivity between the amygdala and multiple frontal regions. Conclusion: Resilient and vulnerable individuals exhibit structural and functional differences in multiple frontal and limbic regions. However, further systematic longitudinal research incorporating environmental factors is required to validate the current findings.